2014
DOI: 10.1080/15715124.2014.885439
|View full text |Cite
|
Sign up to set email alerts
|

How to integrate scientific models in order to switch from flood control river management to multifunctional river management?

Abstract: International audienceSince 2000, the European Water Framework Directive has required managers to restore water bodies to good ecological status, including rivers that have been substantially anthropomorphized, i.e. the vast majority of rivers in France. This obligation creates situations, such as removal of mill sluice gates and strong resistance from local stakeholders that must be addressed by governmental agencies and local elected officials. Seine watershed researchers have suggested using a hydraulic mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Together with the general benefits of restoring ecological continuity, stream‐specific quantitative estimates of increase in habitat accessibility obtained through this raster‐based method might provide managers and local decision makers with additional convincing arguments in favour of undertaking stream restoration. Indeed, recently used in a multi‐agent platform, connectivity estimates have contributed to overcome water use conflicts by providing a shared vision of the river (Carre et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Together with the general benefits of restoring ecological continuity, stream‐specific quantitative estimates of increase in habitat accessibility obtained through this raster‐based method might provide managers and local decision makers with additional convincing arguments in favour of undertaking stream restoration. Indeed, recently used in a multi‐agent platform, connectivity estimates have contributed to overcome water use conflicts by providing a shared vision of the river (Carre et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in [20], the participants where Hmong people from northern Thailand and they had no Usability of Computerised Gaming Simulation for Experiential Learning DOI: http://dx.doi.org/10.5772/intechopen.97303 experience whatsoever of using computer screens. In another application, in Grand Morin river basin in France [25], the participants to a second phase of the project were elderly riverside residents who were not familiar with computers. Similarly, in the LittoSIM game, which involves teams of several people, each with a tablet computer, we observed that often the person most comfortable with computers will take care of the tasks that are performed on the tablet.…”
Section: Accessibility Of the Computing Environmentmentioning
confidence: 99%
“…Other experimental sites include mid-order streams (3 and 4), such as the Grand Morin River (III on Fig. 1), for which social experiments among river users have been undertaken [50,90], and the Orge River, a suburban river in the Paris region with a high population density, where many analyses of legacy and emerging contaminants have been carried out (IV in Fig. 1) [85].…”
Section: The Spatio-temporal Scales Of the Research Themes Selected In This Publicationmentioning
confidence: 99%